Macy McMillan and the rainbow goddess - Green, Shari, 1963- (Toronto, Ontario, Canada : Pajama Press Inc., 2017)
Olivia has been Macy McMillan's best friend ever since Macy transferred to Hamiliton Elementary from Braeside School for the Deaf. But then their sixth grade teacher assigned that embarrassing family tree project, and Olivia made a joke about Macy's father, and now neither girl is speaking--signing--to the other. It couldn't have happened at a worse time. With her mother getting married and an ugly For Sale sign jammed into their yard, Macy could really use a best friend right now. But it seems the only person who has time for her these days is Iris Gillan from next door. And it's not like a crabby old woman who doesn't even know sign language is going to be any comfort. Right?
For readers about 8 to 12.
Keywords: Deaf children -- Juvenile fiction; Girls -- Juvenile fiction; Female friendship -- Juvenile fiction; Stepfamilies -- Juvenile fiction; Neighbors -- Juvenile fiction; Novels in verse; Deaf people -- Juvenile fiction; Neighbors -- Juvenile fiction; Friendship -- Juvenile fiction; Novels in verse; Deaf people -- Juvenile fiction; Friendship; Deaf children; Neighbors; Stepfamilies; Novels in verse; Juvenile works; Novels in verse; Fiction